2002
DOI: 10.1017/s0144686x02008528
|View full text |Cite
|
Sign up to set email alerts
|

Active Ageing and education in mid and later life

Abstract: Demographic change means not only that there will be a larger number of very old people in the future, but also that the median age of the population is moving upwards. At the same time, technological, economic and political change has destabilised labour markets. In the face of growing unemployment, and influenced by early retirement policies in some countries, labour market attachment for people in mid and later life, especially men, has been falling. Increasing costs of supporting ‘non-productive’ mid-lifer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(67 citation statements)
references
References 0 publications
5
60
0
2
Order By: Relevance
“…Training and the development of skills may assist older women to participate in the labour market on more equal terms with men and younger employees. It can also assist in helping people with the transition to retirement and older age, in enhancing quality of life and social inclusion rather than simply focussing on employment (Davey 2002). …”
Section: Education and Trainingmentioning
confidence: 99%
“…Training and the development of skills may assist older women to participate in the labour market on more equal terms with men and younger employees. It can also assist in helping people with the transition to retirement and older age, in enhancing quality of life and social inclusion rather than simply focussing on employment (Davey 2002). …”
Section: Education and Trainingmentioning
confidence: 99%
“…There is a growing literature on this topic, but the field is still in its infancy (Davey, 2002, Clarke & Warren, 2007, HuiChuan, 2007. Bowling (2008) reports an interview survey with 337 people aged 65+ living in Britain.…”
Section: Introductionmentioning
confidence: 99%
“…' Both Walker (2002) and Holstein and Minkler (2007) agree on the vital importance of avoiding the imposition of top-down generalities by attending to the specificities of the various lived realities of older people, positive and negative alike. There is a need for 'insights into fundamental questions about how and why we experience old age in very particular ways' (Holstein and Minkler, 2007: 22), and Walker (2002Walker ( , 2006 stresses the importance of diversity and inclusion of understandings of 'activity' that might deviate from those embodied in policy norms, many of which are oriented towards economics (Davey, 2002). Clarke & Warren (2007), Reed et al (2003) and Howarth (1998) have observed that expectations around active ageing are typically defined by policy makers, service planners and allied researchers, and that these may diverge from the modes of thought of older people themselves.…”
Section: Introductionmentioning
confidence: 99%
“…ej., Alfageme, 2007) como internacional (p. ej., Davey, 2002), las mujeres son las que más resultados positivos perciben de estos.…”
Section: Discussionunclassified